Arterial hypertension and stiffness in women of different age groups and reproductive status - O. S. Ivanova; E. Y. Maychuk; I. V. Voevodina; I. A. Makarova; E. V. Akatova; A. I. Zavyalova; O. P. Nikolin (Евразийский Кардиологический Журнал, 2023)
Objective:  study of the relationship between  arterial hypertension  and arterial stiffness  in women  to identify potential markers of target organ damage and therapeutic targets of antihypertensive therapy.Materials  and methods: the study involved 161 women who were divided into three groups depending on age and reproductive function. Group 1 consisted of 52 women  aged 18 to 30; group 2 – 54 women  aged 31 years before menopause; 3rd group – 55 women in the postmenopausal period. All women were questioned,  clinical examination, determination of anthropometric data, measurement of carotid-femoral pulse wave velocity, determination of arterial stiffness by volumetric sphygmography, 24-hour blood  pressure monitoring with assessment of aortic stiffness and characteristics of the central pulse wave.Results: 24-hour blood pressure monitoring revealed arterial hypertension  in 38 (34,8%)  women: 15 (27,8%)  women in the 2nd group and 23 (41,8%)  women in the 3rd group. Correlation analysis revealed the most significant correlations between  the presence  of arterial hypertension (R=0,45-0,71;   p<<0,01)  with central aortic pressure, double product index and average daily aortic pulse wave velocity  in the aorta (PWVao),  regardless  of the state reproductive  function. For women  of reproductive  age  with arterial hypertension,  the  ambulatory vascular stiffness  index (AASI: R=0,36;  p=0,01)  is more  significant, while in the  menopausal period, the  arterial stiffness  index  (ASI:  R=0,33;  p=0,01). Correlation analysis did not reveal significant relationships  between  carotid-femoral pulse wave velocity and cardio-ankle  vascular index (CAVI) with arterial hypertension in women  of the 2nd and 3rd groups.  The relationship between carotid-femoral  pulse wave velocity and arterial hypertension  in women  was confirmed by analysis of variance (p=0,007).Conclusion: Central aortic  pressure,   carotid-femoral   pulse  wave  velocity, AASI, ASI, PWVao  – direct and indirect indicators  of arterial stiffness  – are interconnected   with  the  presence   of arterial  hypertension   in  women   of reproductive and menopausal age. In this regard, these indicators  are potential markers of target organ damage  in arterial hypertension.